2018
DOI: 10.1093/femsyr/foy104
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of requirements for anaerobic xylose fermentation by engineered, non-evolved Saccharomyces cerevisiae strains

Abstract: Expression of a heterologous xylose isomerase, deletion of the GRE3 aldose-reductase gene and overexpression of genes encoding xylulokinase (XKS1) and non-oxidative pentose-phosphate-pathway enzymes (RKI1, RPE1, TAL1, TKL1) enables aerobic growth of Saccharomyces cerevisiae on d-xylose. However, literature reports differ on whether anaerobic growth on d-xylose requires additional mutations. Here, CRISPR-Cas9-assisted reconstruction and physiological analysis confirmed an early report that this basic set of gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 79 publications
(113 reference statements)
2
9
0
Order By: Relevance
“…Altogether, these results emphasize the important impact of the intracellular CO 2 /HCO 3 - pool for metabolic flux distribution, which is especially relevant in engineered strains suffering from lower endogenous CO 2 production rates as exemplified by PDHC-deficient strains in this study, but also by the performance of pentose-fermenting yeast and E. coli strains (57, 58). Consequently, the lack of an important by-product, like CO 2 released by the PDHC complex, may have a significant impact on cellular metabolism and growth, especially on glycolytic substrates demanding a high flux via the anaplerotic reactions.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Altogether, these results emphasize the important impact of the intracellular CO 2 /HCO 3 - pool for metabolic flux distribution, which is especially relevant in engineered strains suffering from lower endogenous CO 2 production rates as exemplified by PDHC-deficient strains in this study, but also by the performance of pentose-fermenting yeast and E. coli strains (57, 58). Consequently, the lack of an important by-product, like CO 2 released by the PDHC complex, may have a significant impact on cellular metabolism and growth, especially on glycolytic substrates demanding a high flux via the anaplerotic reactions.…”
Section: Discussionsupporting
confidence: 60%
“…The critical impact of CO 2 /HCO 3 - levels may become especially evident under conditions when the endogenous CO 2 production rate becomes limiting. This was nicely demonstrated by a recent study of Bracher et al who could show that long lag phases of engineered, but non-evolved Saccaromyces cerevisiae strains during xylose fermentation could be avoided by sparging the bioreactor cultures with CO 2 /N 2 mixtures (57). Alternatively, the addition of L-aspartate, whose transamination provides oxaloacetate refueling the TCA, completely abolished the long adaptation phase of the respective yeast strains.…”
Section: Discussionmentioning
confidence: 88%
“…Consequently, a repressed glyoxylate shunt due to glucose catabolite accumulation probably also accounts for oxaloacetate depletion in PDHC-deficient strains; this is especially problematic for the ΔaceE Δpyc strain, which cannot complement this depletion by anaplerotic pathways due to lower intracellular CO 2 /HCO 3 levels. Taken together, these results emphasize the important impact of the intracellular CO 2 /HCO 3 pool on metabolic flux distribution, which is especially relevant in engineered strains exhibiting lower endogenous CO 2 production rates, as exemplified by PDHC-deficient strains in this study, but also by the performance of pentose-fermenting yeast and E. coli strains (56,57). Consequently, the lack of an important by-product, such as CO 2 released by the PDHC, may have a significant impact on cellular metabolism and growth, especially on glycolytic substrates demanding high flux via anaplerotic reactions.…”
Section: Figsupporting
confidence: 63%
“…The critical impact of CO 2 /HCO 3 levels may become especially evident under conditions where the endogenous CO 2 production rate becomes limiting. This was nicely demonstrated by a recent study of Bracher et al, who showed that long lag phases of engineered, but nonevolved, Saccharomyces cerevisiae strains during xylose fermentation could be avoided by sparging the bioreactor cultures with CO 2 -N 2 mixtures (56). Alternatively, the addition of L-aspartate, whose transamination provides oxaloacetate, which refuels the TCA cycle, completely abolished the long adaptation phase of the respective yeast strains.…”
Section: Figmentioning
confidence: 89%
“…A multi-copy plasmid leading to overproduction of the PirXI protein has also been used for enhanced xylose metabolism [16]. The engineering of yeast strains showing faster xylose metabolism is an important challenge in the pursuit of strain improvement for second-generation bioethanol production [17][18][19][20].…”
mentioning
confidence: 99%